2010
DOI: 10.1007/s11442-010-0804-7
|View full text |Cite
|
Sign up to set email alerts
|

Transmutation of ancient settlements and environmental changes between 6000–2000 aBP in the Chaohu Lake Basin, East China

Abstract: Based on the temporal-spatial distribution features of ancient settlement sites from the middle and late Neolithic Age to the Han dynasty in the Chaohu Lake Basin of Anhui Province, East China, using the methods of GIS combined with the reconstructed paleoenvironment by the records of lake sediment since Holocene, the transmutation of ancient settlements with response to environmental changes in this area has been discussed. Studies show that the main feature of transmutation of ancient settlements from the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…ka.B.P., the climate was cold and dry with obvious fluctuations, and the natural environment was subjected to prolonged human influence. Based on geomorphology and remote sensing (RS) image analysis of this area, the 10 m contour above present Wusong elevation represents the maximum level of the Chaohu Lakeshore (Gao, 2006), which is also supported by archaeology Wu et al, 2010). However, contraction of the lake started around 5.0 cal.…”
Section: Evolution Of Large Freshwater Lakesmentioning
confidence: 87%
See 3 more Smart Citations
“…ka.B.P., the climate was cold and dry with obvious fluctuations, and the natural environment was subjected to prolonged human influence. Based on geomorphology and remote sensing (RS) image analysis of this area, the 10 m contour above present Wusong elevation represents the maximum level of the Chaohu Lakeshore (Gao, 2006), which is also supported by archaeology Wu et al, 2010). However, contraction of the lake started around 5.0 cal.…”
Section: Evolution Of Large Freshwater Lakesmentioning
confidence: 87%
“…The temporal-spatial pattern of regional climate and environment in the Yangtze River Valley is thought to be controlled by the dual influence of the East Asian monsoon and the Southwest monsoon. However, from previous research Yang et al, 1996;Cai et al, 2001;Shao et al, 2006;Yin et al, 2006;Zhao et al, 2007;Overpeck and Cole, 2008;Ma et al, 2009;Wu et al, 2010), it could also be concluded that Holocene climate change occurred in response to solar radiation changes that affected the whole Yangtze River Valley (Fig. 2).…”
Section: Referencesmentioning
confidence: 88%
See 2 more Smart Citations
“…Many researches indicate that rapid change of Holocene environment includes natural environmental evolution and crossing influences of human activities. How to research compound influences on nature and humanity is a complicated and difficult scientific issue (Marchant and Hooghiemstra, 2004;Mercuri, 2008;Rosen, 2008;Hoffmann et al, 2010;Wu et al, 2010). One of the solutions is that, selecting a typical area with human activities and natural environmental evolution, and then combining temporal-spatial distribution of Holocene human sites with natural continuous sediment of lacustrine peat deposition for comprehensive and integrated comparison research.…”
Section: Introductionmentioning
confidence: 99%